Beyond Paralinguistic Responsiveness: How Does a Pre-schooler Address His Gestural Communication? - Didik Rinan Sumekto; Taufiqulloh Taufiqulloh (Universitas Pancasakti Tegal, 2026)
This study ethnographically portrays the pre-schooler's gestures responsiveness with his existing autism spectrum disorder (ASD) and speech delay. This ethnographic study naturally accomplished the insightful qualitative analysis and interpretation observation and videotape recordings to address Levi's daily communication that became a single case study. Levi's paralinguistic responsiveness measured some portrayable emotions and behaviours including responses, requests, and complaints that empirically conveyed his egocentrics, obliviousness, self-consciousness, self-reliance, and reticence rhythms. The findings recalled the eduistic language annotator (ELAN) results of depicting the annotations on chronological transcriptions, generic, and media synchronization modes, from which partially showed Levi's emotions and behaviours as indicated his gesturally paralinguistic responsiveness. This fact addressed how a pre-schooler with his ASD and speech delay emotionally and behaviourally derives the responses, requests, and complaints as major nonverbal language communications. This study recommends other comparably quantitative and qualitative instruments that are subject to consider the neuroscience and psychometric assessments of having accomplished research variances, particularly on the fields of paralinguistic attribution.